Burkitt lymphoma and lactic acidosis: A case report and review of the literature. Issue 4 (21st February 2021) - Looyens, Carole; Giraud, Raphael; Neto Silva, Ivo; Bendjelid, Karim
Abstract: Type A lactic acidosis is a potentially life‐threatening complication in critically ill patients and is the hallmark of a shock state as a result of tissue hypoperfusion and dysoxia. Type B lactic acidosis results from mechanisms other than dysoxia and is a rare condition in patients with solid tumors or hematological malignancies. We present a case of a 60‐year‐old man with lactic acidosis who was found to have a Burkitt lymphoma related to a posttransplant lymphoproliferative disorder. Lactagenic cancers are characterized by increased aerobic glycolysis and excessive lactate formation, a phenomenon described by Warburg in 1923 that is correlated with cancer aggressiveness and poor survival. There is increased glucose utilization with the purpose of lactagenesis under fully oxygenated conditions, as lactate seems to be a potent signaling molecule for angiogenesis, immune escape, cell migration, metastasis and self‐sufficient metabolism, which are five essential steps of carcinogenesis. Type B lactic acidosis in association with malignancies carries an extremely poor prognosis. Currently, effective chemotherapy seems to be the only hope for survival. Abstract : Lactagenic cancers are characterized by increased aerobic glycolysis and excessive lactate formation, a phenomenon described by Warburg in 1923 that is correlated with cancer aggressiveness and poor survival. Type B lactic acidosis in association with malignancies carries an extremely poor prognosis. Currently, effective chemotherapy seems to be the only hope for survival.